ERYTHEMATOUS AND SCALING SKIN DISORDERS. I. Pityriasis rosea, eczematide, pityriasis lichenoides. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Scaling is an elementary lesion of the skin, that follows an erythema persisting for some days. Scaling is due to an accelerated reproduction of the epidermal cells, which is caused by the vasodilatation of the papillary plexus characterizing erythema. Scaling may be observed during the remission phase of numerous skin diseases, from actinic erythema to exanthemata. On the other hand, in erythematous and scaling skin disorders, desquamation is an important component precociously superimposed to intensely erythematous patches. In this chapter we will treat pityriasis rosea, eczematides, pityriasis lichenoides, patch parapsoriasis and psoriasis. We will not talk about pityriasis versicolor, which is very rare in childhood. Even patch parapsorias does not practically exist in the first decade, but some cases may occur in the second decade. Psoriasis is slightly less frequent in children as compared with adults. Pityriasis rosea and pityriasis lichenoides affect the same age group. They are rare before the third year and after the third decade. Eczematides are more frequent in children than in adults.